Hubungan Preeklamsi Dengan Kejadian Berat Bayi Lahir Rendah (BBLR) Di RSUP Haji Adam Malik Medan - Elvina Sari Sinaga; Aminah Aminah (Jurnal Indragiri Penelitian Multidisiplin, 2022)
Maternal Mortality Rate (MMR) in developing countries in 2015 was 239 per 100,000 live births, is still very high compared to developed countries with an MMR of 12 per 100,000 live births. Indonesia is one of the developing countries with high MMR is still very high at 305 per 100,000 live births in 2015. Prevalence preeclampsia in developed countries 1.3-6%, while in developing countries 1.8-18%. Indonesia prevalence of preeclampsia 5.3% (Pusdatin Kemenkes RI, 2014). The results of Riskesdas in 2018 stated that the percentage of LBW in Indonesia is 6.2% and North Sumatra is 4.2%. Proportion of causes The highest neonatal mortality was asphyxia 35.3% and LBW 27.0% (Kemenkes RI, 2019).This research analytic correlation with cross sectional design, namely to determine the relationship preeclampsia with the incidence of LBW in H. Adam Malik Hospital. Data analysis results of statistical tests using the chi square test obtained p value of 0.001 <0.05 and X2 = 24.38 means that there is a relationship between mothers who experience preeclampsia with the incidence of baby weight low birth, at the 95% CI level of 4.50-50.02, it means that mothers who experience preeclampsia 4-50 times the possibility of giving birth with Low Birth Weight (LBW) in RSUPH. Adam Malik Medan Starting in 2017-2019